The origins and development of English medieval townhouses operating commercially on two storeys - Harris, R; Harris, Roland (1994)
Over the last thirty years the study of the English medieval townhouse has not developed on a par with medieval archaeology, or urban history. This thesis combines the evidence of standing buildings, archaeological excavation, antiquarian records, and documentary sources, to reconsider the form of townhouses used in the distributive trades, and, in particular, it examines the evidence for the origins of townhouses operating commercially on two storeys (split-level townhouses), and their relationship to the raised walkways of the Chester Rows. The Romanesque townhouse in England has not been the subject of original research since the 1930s, so in the early parts of the thesis the corpus of evidence is sorted into broad categories: the urban manor-like property; the stone-built chamber block at the rear of a timber-built range on the streetfront; the grand suburban house; the commercial townhouse on the streetfront (the ground-level townhouse); the split-level warehouse; and the split-level townhouse. The twelfth-century origins of the split-level townhouse are examined, and it is clear that prototypical or even fully developed examples of the split-level townhouse exist as early as their ground-level counterparts. Despite a general dearth of early thirteenth-century buildings, it can be seen that by the mid to late thirteenth century, the split-level townhouse was dominant in the principal streets of English towns, almost to the total exclusion of other house types. Throughout the thirteenth and fourteenth centuries, the split-level design was adapted to the highly commercial and continuously built-up streets and the unusual topography of Chester, so that the upper-level shops were linked by a raised gallery. Although split-level townhouses have proved elusive on the continent, examples are known in the Zähringen towns of modern Switzerland: several of these towns have also developed elevated walkways. There can be little doubt that the split-level townhouse and its variants were the result of commercial pressure, and an insatiable demand, not found again after the early to mid fourteenth century, for numerous small-scale retail units and undercrofts.